Extensive hybridization between two Andean warbler species with little divergence in mtDNA (2018)
Studying processes occurring when closely related taxa achieve secondary contact, such as hybridization, is important to fully understand how species are formed and maintained over time. However, studying these processes has been largely overlooked in studies of avian speciation in the Andes, which have focused mainly on understanding the role of barriers promoting divergence. In this study I characterized a hybrid zone between two Andean birds, Myioborus ornatus and Myioborus melanocephalus, using genetic, coloration, and song data. Geographic ranges of these species abut around the Colombia-Ecuador border and specimens from the region exhibit intermediate phenotypes suggesting hybridization, but descriptions of patterns of variation were lacking. I conducted fieldwork to collect specimens and obtain recordings of vocalizations across a ca. 400 km transect around the Colombia-Ecuador border and localities away from the putative hybrid zone. I described variation in head color pattern, ventral coloration and tail pattern using specimens. To describe acoustic variation, I measured spectral and temporal parameters from songs. To describe genetic variation, I sequenced the gene ND2. I extended genetic sampling to encompass all main regions where these species occur to describe phylogeographic structure. The hybrid zone is characterized by low genetic structure and is ~200 km wide based on head coloration. Intermediate plumage phenotypes are the most common across the hybrid zone, suggesting extensive hybridization. Song duration is the only acoustic parameter that varies across the sampling transect. Specimens from the hybrid zone and Ecuadorian populations of M. melanocephalus belong to the same genetic group as M. ornatus, and there is low genetic structure within this group characterized by high diversity in plumage phenotypes. Patterns of variation in plumage suggest that selection against hybrids is not strong, a hypothesis that should be tested using genomic data